THE THEOLOGY OF SPIRITUALITY OF THE CHRISTIAN TEACHER FOR THE EFFECTIVENESS OF THEIR MINISTRY - Mawikere, Marde Christian Stenly; Hura, Sudiria (Sekolah Tinggi Agama Kristen Arastamar Grimenawa Jayapura, 2025)
This study aims to analyse the role of spirituality in enhancing the effectiveness of Christian teachers' ministry. Through a literature review, the research explores the relationship between deep spirituality and a teacher's ability to teach and serve students, families, churches, and communities. The findings indicate that authentic and consistent spirituality plays a crucial role in shaping the character of Christian teachers, who not only teach with knowledge but also with a heart and integrity grounded in Christian faith. Exemplary living, spiritual discipline, and the ability to overcome contemporary challenges are key factors that enhance the effectiveness of teaching. This research concludes that strong spirituality not only enriches teaching but also strengthens the positive impact on the development of students' character and the surrounding community.